2021
DOI: 10.52225/narra.v1i3.48
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of persistent neuromuscular symptoms and the possible pathomechanisms in COVID-19 recovered individuals: A systematic review and meta-analysis

Abstract: This study was conducted to determine the prevalence of prolonged neuromuscular symptoms, including fatigue, anosmia, headache, myalgia, and joint pain in COVID-19 survivors hospitalized with mild, moderate, or severe infections worldwide. The search was conducted up to January 30th, 2021 using three databases (PubMed, Scopus, and Web of Science) to identify potentially eligible studies. Data on study characteristics, follow-up characteristics, and severity of COVID-19 during hospitalization were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 109 publications
(131 reference statements)
0
22
0
Order By: Relevance
“…This systematic review was conducted in accordance to the Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA) guidelines 33 as previously used elsewhere. 34,35 Articles were included in this review, when the following criteria were fulfilled: 1). The sample was at least coffee husk, coffee silverskin, coffee pulp, coffee parchment, or the cascara (pulp and outer skin); 2).…”
Section: Study Setting and Eligibility Criteria Of Studiesmentioning
confidence: 99%
“…This systematic review was conducted in accordance to the Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA) guidelines 33 as previously used elsewhere. 34,35 Articles were included in this review, when the following criteria were fulfilled: 1). The sample was at least coffee husk, coffee silverskin, coffee pulp, coffee parchment, or the cascara (pulp and outer skin); 2).…”
Section: Study Setting and Eligibility Criteria Of Studiesmentioning
confidence: 99%
“…Infiltrating monocytes, macrophages, and neutrophils are clearly found in both lungs, accompanied by multinucleated syncytial cells infiltration in the alveoli that characterized by amphiphilic granular cytoplasm, large nuclei, and prominent nucleoli indicating viral cytopathic alters (27)(28)(29)(30)(31). Additionally, myocardial infarction, kidney damage, and persistent symptoms, such as depression, anxiety, palpitations, chest pain, sleep difficulty, dizziness, and weight loss, also represent the pathological features of critically COVID-19 cases (27)(28)(29)(30)(31)(32). The immune profile in COVID-19 patients has been well reviewed, which shows dysfunction in both the innate and adaptive immune (33,34).…”
Section: Pathological Characteristics Of Covid-19mentioning
confidence: 99%
“…Generally, the pathological feature of COVID-19 is bilateral diffuse alveolar damage with evidence of neutrophil extracellular traps, fibrin thrombi, and activated platelets in the vessels ( 25 , 26 ). Infiltrating monocytes, macrophages, and neutrophils are clearly found in both lungs, accompanied by multinucleated syncytial cells infiltration in the alveoli that characterized by amphiphilic granular cytoplasm, large nuclei, and prominent nucleoli indicating viral cytopathic alters ( 27 31 ). Additionally, myocardial infarction, kidney damage, and persistent symptoms, such as depression, anxiety, palpitations, chest pain, sleep difficulty, dizziness, and weight loss, also represent the pathological features of critically COVID-19 cases ( 27 32 ).…”
Section: Pathological Characteristics Of Covid-19mentioning
confidence: 99%
“…Noteworthily, persistent long COVID symptoms like anxiety, prolonged depression, chest pain, palpitations, dizziness and hair loss as well as prolonged neuromuscular symptoms (fatigue, anosmia, headache, myalgia and joint pain) are a cause of grave concern in COVID‐19 patients even after two weeks of recovery. 9 , 10 In a systematic review and meta‐analysis, the authors explored the association between delirium and poor prognosis in COVID‐19 patients and suggested that the delirium in older patients can be an important presenting symptom of COVID‐19 implicating poor outcomes and high risk of mortality. 11 …”
Section: Introductionmentioning
confidence: 99%